The Devolopmet Perkembangan Nilai Tukar Petani Ternak Ruminansia Besar dan Faktor-faktor yang Mempengaruhinya di Nusa Tenggara Timur: Nilai Tukar Petani Ternak Ruminansia Besar - Johny Agustinus Koylal; Stefanus M. Kuang; Jemseng C. Abineno (Politeknik Negeri Lampung., 2023)
The livestock sector of East Nusa Tenggara has a large multiplier impact on the welfare and absorption of labor. One approach used to measure the welfare of farmers is the farmer's exchange rate. The study aims to examine the development of the exchange rate of large ruminant farmers in East Nusa Tenggara with quantitative descriptive and the factors that influence it with a multiple regression model. The data used are the exchange rate of livestock sector farmers and the exchange rate of large ruminant farmers during the period from January 2017 to December 2020 obtained from the Central Statistics Agency. The results showed that although the average exchange rate of large ruminant farmers in East Nusa Tenggara was lower than the National average, the trend was increasing. In part, only the wages of farmworkers have a significant effect on the exchange rate of large ruminants and collectively household consumption expenditures; the price of seedlings; prices of medicines and feed; land rent, taxes, and others; transportation costs; the cost of adding capital goods; and the wages of farmworkers are a significant explanation of the exchange rate of large ruminant cattle farmers. Keywords: livestock, ruminants, breeders, welfare